Three new species of Stenella - and KAMAL, SAPNA CHAUDHARY, NIDHI SHARMA (Indian Phytopathology, 2012)
Three new species Stenella lamiacearum, S. polyalthiae and S. rubiacearum occurring on living leaves of Teucrium sp., Polyalthia suberosa and Wendlandia tinctoria respectively are described.